2017
DOI: 10.1039/c6fo01655c
|View full text |Cite
|
Sign up to set email alerts
|

Lactucaxanthin – a potential anti-diabetic carotenoid from lettuce (Lactuca sativa) inhibits α-amylase and α-glucosidase activity in vitro and in diabetic rats

Abstract: Intestinal and pancreatic α-amylase and α-glucosidase inhibitors offer an approach to lower the levels of post-prandial hyperglycemia through the control of dietary starch breakdown in digestion. This study hypothesized that lactucaxanthin (Lxn) in lettuce (Lactuca sativa) inhibits the activity of α-amylase and α-glucosidase. In this study, the interaction of Lxn with α-amylase and α-glucosidase in silico and its inhibitory effect on these enzymes were studied using in vitro and STZ-induced diabetic rat models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Aqueous radish sprout extract was also reported to cause 50% reduction of AG activity at the concentration of 60.7 ± 1.2 mg/mL [59]. Lactucaxanthin, a carotenoid extracted from lettuce, showed AG inhibition with an IC 50 value of 1.84 mg/mL, while acarbose showed a value of 16.19 µg/mL [60]. Cucurbits are another major vegetable crops that possess inhibitory activity against AG enzymes.…”
Section: Common Vegetables With Ag Inhibitory Activitiesmentioning
confidence: 99%
“…Aqueous radish sprout extract was also reported to cause 50% reduction of AG activity at the concentration of 60.7 ± 1.2 mg/mL [59]. Lactucaxanthin, a carotenoid extracted from lettuce, showed AG inhibition with an IC 50 value of 1.84 mg/mL, while acarbose showed a value of 16.19 µg/mL [60]. Cucurbits are another major vegetable crops that possess inhibitory activity against AG enzymes.…”
Section: Common Vegetables With Ag Inhibitory Activitiesmentioning
confidence: 99%
“…Data from a meta-analysis included a study from 1966 to 2014 that demonstrated that a high intake of fruit, particularly berries, and yellow, cruciferous, green leafy vegetables or their fibers, is negatively linked to type 2 diabetes [ 291 ]. As an example, lactucaxanthin (Lxn), a carotenoid in lettuce ( Lactuca sativa ), suppresses α -amylase and α -glucosidase activity both in vitro and in diabetic rats [ 292 ]. Such findings highlight the role of unique complexes of bioactive components in fruits and vegetables.…”
Section: Diet Ameliorates Oxidative Stress-induced Diseasesmentioning
confidence: 99%
“…DM is the most common chronic disease characterized by elevated blood glucose levels [1]. Long-term exposure to high blood glucose levels results in production of reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%